2013
DOI: 10.1088/0004-637x/764/1/41
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Binary Evolution Across Cosmic Time

Abstract: High redshift galaxies permit the study of the formation and evolution of X-ray binary populations on cosmological timescales, probing a wide range of metallicities and star-formation rates. In this paper, we present results from a large scale population synthesis study that models the X-ray binary populations from the first galaxies of the universe until today. We use as input to our modeling the Millennium II Cosmological Simulation and the updated semi-analytic galaxy catalog by Guo et al. (2011) to self-co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
309
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(342 citation statements)
references
References 80 publications
31
309
2
Order By: Relevance
“…At lower luminosities, the XLF of star-forming galaxies is comparable to, or even exceeds, the AGN XLF, in agreement with Vito et al (2016), who found that the X-ray emission in galaxies individually undetected in the 7 Ms CDF-S is mostly due to XRB. Similar conclusions are reached by scaling the star-formation rate functions (SFRF, i.e., the comoving space densities of galaxies per unit star-formation rate) from Smit et al (2012) and Gruppioni et al (2015), at z ≈ 3.5 and 4, respectively, into XLF using the best-fitting, redshift-dependent Fragos et al (2013) and Lehmer et al (2016) relations.…”
Section: The Agn Xlf At High Redshiftsupporting
confidence: 62%
“…At lower luminosities, the XLF of star-forming galaxies is comparable to, or even exceeds, the AGN XLF, in agreement with Vito et al (2016), who found that the X-ray emission in galaxies individually undetected in the 7 Ms CDF-S is mostly due to XRB. Similar conclusions are reached by scaling the star-formation rate functions (SFRF, i.e., the comoving space densities of galaxies per unit star-formation rate) from Smit et al (2012) and Gruppioni et al (2015), at z ≈ 3.5 and 4, respectively, into XLF using the best-fitting, redshift-dependent Fragos et al (2013) and Lehmer et al (2016) relations.…”
Section: The Agn Xlf At High Redshiftsupporting
confidence: 62%
“…These codes rely on precomputed grids of detailed stellar models and approximate treatments of the physical processes as described below. Despite the approximations, studies with this and similar codes based on the same philosophy have enabled insights into the many exotic phenomena resulting from lowand high-mass interacting binaries (e.g., recent work by Izzard et al 2004Izzard et al , 2006Izzard et al , 2009Ruiter et al 2009Ruiter et al , 2014Mennekens et al 2010;Abate et al 2013;de Mink et al 2013de Mink et al , 2014Fragos et al 2013;Vanbeveren et al 2013;Claeys et al 2014;Kochanek et al 2014;Mennekens & Vanbeveren 2014;Schneider et al 2014Schneider et al , 2015Toonen et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, reduced wind mass losses in low-metallicity environments lead to reduced angular momentum losses and to overall tighter binary orbits, which in turn increase the ratio of Roche-lobe overflow versus wind-fed HMXBs. The former mass transfer mechanism is significantly more efficient, and produces a more luminous HMXB population (Fragos et al 2013b). Finally, low metallicity massive stars tend to expand later in their evolution compared to their high metallicity counterparts, thus interacting with their companions for the first time and entering the common envelope phase while having more massive cores and less bound envelopes that can be easily expelled.…”
Section: Mass-metallicity Relationmentioning
confidence: 99%
“…We have calculated the intrinsic (unabsorbed) spectral energy distribution (SED) of the global compact binary population following the prescriptions presented by Fragos et al (2013b), which treat separately neutron stars and black hole binaries in different spectral states -a high-soft state where the spectrum is dominated by the thermal emission from the disk, and a low-hard state where the spectrum is dominated by a power-law component. The transition between low-hard and high-soft states in both cases is observed to occur at a luminosity of about 5% L Edd ( (2010) compact binary RXTE samples are 0.63±0.09 and 0.51±0.13 for neutron stars and black hole binaries in the high-soft state, and 0.27 ± 0.09 and 0.33 ± 0.10 for neutron stars and black hole binaries in the low-hard state, respectively (Fragos et al 2013b).…”
Section: Mass-metallicity Relationmentioning
confidence: 99%